2014
DOI: 10.1007/s13277-014-2526-4
|View full text |Cite
|
Sign up to set email alerts
|

C-Myc-activated long noncoding RNA CCAT1 promotes colon cancer cell proliferation and invasion

Abstract: Recently, more and more evidence are rapidly accumulating that long noncoding RNAs (lncRNAs) are involved in human tumorigenesis and misregulated in many cancers, including colon cancer. LncRNA could regulate essential pathways that contribute to tumor initiation and progression with their tissue specificity, which indicates that lncRNA would be valuable biomarkers and therapeutic targets. Colon cancer-associated transcript 1 (CCAT1) is a 2628 nucleotide-lncRNA and located in the vicinity of a well-known trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(172 citation statements)
references
References 27 publications
9
163
0
Order By: Relevance
“…3,4 Colon cancer-associated transcript 1 (CCAT1), a ~2-kb lncRNA located at chromosome 8q24.21, is first found to be upregulated in colon cancer. 5 Recently, some reports have found that CCAT1 is involved in tumor progression and tumorigenesis in various types of cancers including colon cancer, 6 gastric cancer, 7 and colorectal cancer. 8 The competitive endogenous RNA (ceRNA) mechanism for CCAT1 and microRNAs involving in tumor progression has been reported in some studies, for example, Zhou et al 9 reported the lncRNA CCAT1/miR-490 axis regulated gastric cancer cell migration by targeting hnRNPA1.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Colon cancer-associated transcript 1 (CCAT1), a ~2-kb lncRNA located at chromosome 8q24.21, is first found to be upregulated in colon cancer. 5 Recently, some reports have found that CCAT1 is involved in tumor progression and tumorigenesis in various types of cancers including colon cancer, 6 gastric cancer, 7 and colorectal cancer. 8 The competitive endogenous RNA (ceRNA) mechanism for CCAT1 and microRNAs involving in tumor progression has been reported in some studies, for example, Zhou et al 9 reported the lncRNA CCAT1/miR-490 axis regulated gastric cancer cell migration by targeting hnRNPA1.…”
Section: Introductionmentioning
confidence: 99%
“…As examples, lncRNAs such as CCAT1 [24][25], CCAT2 [26], HOTAIR [27] and MALAT1 [28] are increased in CRC tissues compared to NATs and have been identified as oncogenes. The lncRNAs can regulate the expression of their target genes, activate some signaling pathways, and promote cell proliferation, metastasis, and tumor recurrence [29][30][31][32]. However, lncRNAs such as MEG3, FER1L4 and ncRAN are downregulated in both cancerous tissues and cell lines [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The CCAT1 locus has been presented to harbor a super-enhancer that could control the c-Myc expression. The CCAT1 was demonstrated to interact with a transcriptional enhancer MYC-335 via chromatin looping and consequently, could interact with the MYC-promoter resulting regulation of c-Myc expression in cis (10,27). In addition, knockdown of CCAT1 led to a decrease in c-Myc levels in colon cancer-derived cell lines (28).…”
Section: Ccat1 Expression Level -------------------------------------mentioning
confidence: 99%
“…Previous studies have indicated that CCAT1 is differentially expressed in several types of cancers, including colon cancer, gastric cancer, gall bladder cancer and hepatocellular carcinoma (7)(8)(9). The CCAT1 was identified to be significantly overexpressed and clinically correlated with colon cancer patients' disease stage, lymph node metastasis and survival after surgery (10). In addition, CCAT1 was demonstrated to correlate with overall survival and progression-free survival in breast cancer (11).…”
Section: Introductionmentioning
confidence: 98%